High-Performance Thermoelectric Fabric Based on a Stitched Carbon Nanotube Fiber - Park, Kyung Tae; Lee, Taemin; Ko, Youngpyo; Cho, Young Shik; Park, Chong Rae; Kim, Heesuk (American Chemical Society, 2021)
With the continuous development of flexible and wearable thermoelectric generators (TEGs), high-performance materials and their integration into convenient wearable devices have to be considered. Herein, we have demonstrated highly aligned wet-spun carbon nanotube (CNT) fibers by optimizing the liquid crystalline (LC) phase via hydrochloric acid purification. The liquid crystalline phase facilitates better alignment of CNTs during fiber extrusion, resulting in the high power factor of 2619 mu W m(-1) K-2, which surpasses those of the dry-spun CNT yarns. A flexible all-carbon TEG was fabricated by stitching a single CNT fiber and doping selected segments into n-type by simple injection doping. The flexible TEG shows the maximum output power densities of 1.9 mW g(-1) and 10.3 mW m(-2) at Delta T = 30 K. Furthermore, the flexible TEG was developed into a prototype watch-strap TEG, demonstrating easy wearability and direct harvesting of body heat into electrical energy. Combining high-performance materials with scalable fabrication methods ensures the great potential for flexible/or wearable TEGs to be utilized as future power-conversion devices.